Development and Performance Evaluation of a Smart Fire Alarm System via LoRa Long-Range Communication Technology - SOMUOLA, Mr Sonexay; Thongphanh, Phutsavanh; Dittaphong, Xaysamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
In this Research is focused on Evaluation of performance and development of the Intelligent Fire Alarm System by Using LoRa Long-Range Communication Technology, the Indoor fires are serious disasters causing significant loss of life and property. The traditional wired fire alarm systems have limitations due to high installation and maintenance costs. Especially in the large buildings. While traditional wireless systems often suffer from signal attenuation due to thick building walls. This system aims to design and develop the intelligent fire alarm system by using LoRa (long-range) communication technology. And the research is focused on the low power consumption and long-range transmission, and the system is developed by using an Arduino microcontroller connected to an MQ-2 smoke sensor and a flame sensor, and real-time transmitted data via to a gateway and mobile application. The methodology is evaluated the received signal strength Indicator (RSSI) and response time in two different environments such us: at indoor environment with the obstructions and an open outdoor area. The Experimental results are shown the high system stability with an average RSSI for indoor environment is -78.52 dBm and in the outdoor area is -66.43 dBm, and the packet loss is 0%. Furthermore, the average time response is measured at 39.07 milliseconds. The LoRa technology is suitable for building safety systems. The system can be provided a practical alternative to traditional wired infrastructure, reducing installation costs and accelerating emergency response.